Are Facial Displays Social? Situational Influences in the Attribution of Emotion to Facial Expressions. - Russell, James A.; Carrera, Pilar; Fernández-dols, José Miguel (The Spanish Journal of Psychology, 2002)
Sin resumen
Keywords: expresión facial; reconocimiento de emociones; emoción; expresión emocional